The formation history of Qypchaks in Old and Middle ages - Kosybaev, М.М.; Moldabay, Т.; Zhiyembay, Б. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2023)
The science of Qypchak studies has formed a scientific and bibliographic base on the basis of the scientific works of archaeologists and historians, orientalists and Turkologists collected to this day. On the basis of this scientific literature and source materials, the article discusses the distribution of the Qypchaks and the Kypchak language on the Eurasian continent in the early Middle Ages and the Middle Ages, divided into certain periods. It is clear that the main criterion for the division into these periods is information related to the political and military activities of the Turkic-speaking nomads in this region. The main object of the authors' research is the Qypchaks and the problems of their formation. As a result of the study of the formation of the term Qypchak, it was widely studied by foreign and domestic scientists, its meaning was semantically analyzed, and its semantic boundaries were determined. The article was prepared within the framework of the scientific project AP13068438 «Universal and special in the language of the Armenian-Qypchak monuments».